Apolipoprotein E4 Causes Age- and Sex-Dependent Impairments of Hilar GABAergic Interneurons and Learning and Memory Deficits in Mice - Leung, Laura (Public Library of Science, 2012)
Apolipoprotein (apo) E4 is the major genetic risk factor for Alzheimer's disease (AD). ApoE4 has sex-dependent effects, whereby the risk of developing AD is higher in apoE4-expressing females than males. However, the mechanism underlying the sex difference, in relation to apoE4, is unknown. Previous findings indicate that apoE4 causes age-dependent impairments of hilar GABAergic interneurons in female mice, leading to learning and memory deficits. Here, we investigate whether the detrimental effects of apoE4 on hilar GABAergic interneurons are sex-dependent using apoE knock-in (KI) mice across different ages. We found that in female apoE-KI mice, there was an age-dependent depletion of hilar GABAergic interneurons, whereby GAD67- or somatostatin-positive–but not NPY- or parvalbumin-positive–interneuron loss was exacerbated by apoE4. Loss of these neuronal populations was correlated with the severity of spatial learning deficits at 16 months of age in female apoE4-KI mice; however, this effect was not observed in female apoE3-KI mice. In contrast, we found an increase in the numbers of hilar GABAergic interneurons with advancing age in male apoE-KI mice, regardless of apoE genotype. Moreover, male apoE-KI mice showed a consistent ratio of hilar inhibitory GABAergic interneurons to excitatory mossy cells approximating 1.5 that is independent of apoE genotype and age, whereas female apoE-KI mice exhibited an age-dependent decrease in this ratio, which was exacerbated by apoE4. Interestingly, there are no apoE genotype effects on GABAergic interneurons in the CA1 and CA3 subregions of the hippocampus as well as the entorhinal and auditory cortexes. These findings suggest that the sex-dependent effects of apoE4 on developing AD is in part attributable to inherent sex-based differences in the numbers of hilar GABAergic interneurons, which is further modulated by apoE genotype.